PENGARUH WORK LIFE BALANCE DAN KOMPENSASI TERHADAP LOYALITAS KARYAWAN PADA CV. 88 KOTA BIMA - Jaenab Jaenab; Mulyadin Mulyadin (Sekolah Tinggi Keguruan dan Ilmu Pendidikan (STKIP) Bima, 2024)
The research aims to determine whether work life balance and compensation have a significant effect on employee loyalty at CV. 88 Bima City so that it can provide input to leadership on CV. 88 Bima City. This research is quantitative research and the type of research is associative with the population in this research being all CV employees. 88 Bima City, so the sampling technique was a saturated sample of 37 respondents, while the data collection technique used observation, literature study and questionnaires, referring to a 5 point Likert scale which was then distributed to 37 respondents. The analytical method used in this research is multiple linear regression which is then analyzed using SPSS version 21 for Windows. The results of this research are: 1) There is a significant influence of work life balance on loyalty to CV. 88 Bima City. 2) There is no significant influence of compensation on loyalty to CV. 88 Bima City. 3). There is a significant influence of work life balance and compensation on employee loyalty at CV. 88 Bima City.